Dynamic model of a three-phase asynchronous motor using Matlab/Simulink - K. Bobojanov , Makhsud; N. Tuychiyev, Furqat; X. Rashidov, Nuralibek (PROBLEMS OF ENERGY AND SOURCES SAVING, 2024)
Relevance: The relevance of the work lies in the fact that dynamic models are used to better understand the state of an asynchronous motor in transient and stable operating modes. The theory of displacement along the dq axis is used in the rotor number system to study the dynamics of the motor. The main advantage of the MATLAB/Simulink program is that the simulated electromechanical processes can be easily and quickly implemented using the functional blocks of the program. Controlling three sinusoidal currents is a difficult task, but controlling three currents is not necessary. This task can be simplified by using the Clark and Park transformations for stator currents. First, the three-phase system is converted to a two-phase one using the Clark transformation, and then the conversion to the rotor coordinate system is carried out using the Park transformation. Aim: Consists in the development and research of a generalized model for studying and assessing the dynamic state of a three-phase asynchronous motor using Matlab / Simulink software. Methods: When developing the model, all differential voltages, currents and magnetic fluxes between the stationary stator and the movable rotor were taken into account. Results: Taking into account the above voltages, currents and magnetic fluxes, the Clark Park transformation was carried out, and the dynamic characteristics were obtained and studied. Using the program, dynamic modeling of a 4-pole asynchronous motor with a power of 0.75 kW, power factor cosph=0.76, efficiency η=73%, rated current I1=2.05 A was performed. The developed model is used to study the influence of variable stator resistance, moment of inertia and load moment. The results obtained show that the mechanical characteristics of an asynchronous motor and the rotor speed depend on the rotor resistance and moment of inertia.